Factors Influencing Online Shopping Among Residents in Lasanod Somalia - Mohamed Ali Abdinur (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
Abstract Due to the advancement of technology, many businesses moved from physical locations to online businesses where they do business online. The objective of this paper is to investigate the factors affecting online shopping behavior among residents of Lasanod Somalia. This paper used a quantitative research approach. Data were collected from residents of Lasanod Somalia through questionnaires. 160 questioners were collected from respondents who were selected using a simple random sampling technique. The results showed that factors such as trust, firm reputation, functionality, privacy, reliability, and firm value have an influence on consumers’ online buying behavior. The study found out there is a strong positive correlation between trust and firm reputation with an R-value of .612 and a significant level of .000 which is way below 0.01. This research focused on Lasanod city and cannot be generalized to the whole of Somalia. Furthermore, the sample size was not large.